A new dewatering technique for stingless bees honey - Ramli, A.S. (EDP Sciences, 2017)
One of the problems faced in stingless bee honey storage is spoilage by the fermentation process occurs in honey due to its high water content. There are a few techniques available currently, but they are time consuming and there is excessive heat involved in the process. The temperature of the process must be kept low because excessive heat can deteriorate nutrition value and biochemical content in honey. Hence, a new method of honey dewatering was developed using a Low Temperature Vacuum Drying (LTVD) with induced nucleation technique.The objective of this research is to investigate the performance of a LTVD with induced nucleation to reduce the water content in honey. First, the honey was placed in a pressure vessel, and then air was removed. Then, the honey was slightly heated at 30°C and the water content before and after the experiment was measured by a refractometer. The steps were repeated until the water content reached below 20. It was found that the LTVD method improved the water removal rate significantly with an average of 0.15 of water content per minute. That is 3 times much faster than the conventional method of low temperature heating by Tabouret. Higher temperature during dewatering process improved the dewatering rate significantly. It can be concluded that LTVD is a promising option in tackling the high water content in stingless bee honey issue. © The authors, published by EDP Sciences, 2017.